Michael Longley and Birds - Michalski, Przemysław (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The following essay attempts to shed some light on Michael Longley’s poems about birds, which form a fairly complicated network of mutual enhancements and cross-references. Some of them are purely descriptive lyrics. Such poems are likely to have the name of a given species or a specific individual representative of that species in the title. Others make references to birds or use them for their own agenda, which often transcends the parameters of pure description. Sometimes birds perform an evocative function (“Snow Geese”), prompt the poet to explore the murky mysteries of iniquity (“The Goose”), judge human affairs from the avian vantage (“Aftermath”), or raise ecological problems (“Kestrel”). Most of the time, however, Longley is careful not to intrude upon their baffling otherness. Many of his bird poems are suffused with an aura of subtle yet suggestive eroticism, a conflation of the avian and the amorous.